2013
DOI: 10.1097/rlu.0b013e3182867d56
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis of Diagnostic Value of 99mTc-Ubiquicidin (UBI) Scintigraphy in Detection of an Infectious Process

Abstract: The study demonstrated that Tc-UBI scintigraphy can be used to identify an infectious process with admirable accuracy in early views; however, further investigations are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
0
19
0
3
Order By: Relevance
“…3,4). A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61].…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…3,4). A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61].…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…Ubiquicidin is also produced in activated macrophages and in colonic epithelial cells. In an analysis of the diagnostic performance of 99m Tc-ubiquicidin in infection imaging from studies published between 2004 and 2010, a pooled sensitivity and specificity of 94.5% (95% confidence interval, 91.2%-96.8%) and 92.7% (95% confidence interval, 80%-100%), respectively, were reported (28).…”
Section: Imaging Antibiotic Binding To Microbes: Radiolabeled Antimicmentioning
confidence: 99%
“…Der murine anti-CD3 Antikörper Muromab bindet spezifisch an CD3 und wird als immunsupprimierendes Medikament bei organtransplantierten Patienten zur Prophylaxe einer akuten Abstoßungsreaktion und in der Therapie der Psoriasis Arthritis eingesetzt [106]. 99 Bruijnen et al (2016) untersuchten zudem mit 89 Zr-markiertem Rituximab mittels PET/CT das Therapieansprechen von Patienten mit RA auf eine Rituximab-Therapie. 89 Zr-Rituximab-PET/CT wurde vor und 24 Monate nach Beginn der Behandlung durchgeführt, quantitativ ausgewertet und mit der Anzahl an CD22-positiven B-Lymphozyten in inguinalen Lymphknoten verglichen.…”
Section: Cd3unclassified